Sloppy paired acts as the downstream target of Wingless in the Drosophila CNS and interaction between sloppy paired and gooseberry inhibits sloppy paired during neurogenesis. - Bhat, K.M.; van Beers, E.H.; Bhat, P. (Development, 2000)
Wingless (Wg) and other Wnt proteins play a crucial role in a number of developmental decisions in a variety of organisms. In the ventral nerve cord of the Drosophila embryo, Wg is non-autonomously required for the formation and specification of a neuronal precursor cell, NB4-2. NB4-2 gives rise to a well-studied neuronal lineage, the RP2/sib lineage. While the various components of the Wg-signaling pathway are also required for generating NB4-2, the target gene(s) of this pathway in the signal-receiving cell is not known. In this paper, we show that sloppy paired 1 and sloppy paired 2 function as the downstream targets of the Wg signaling to generate the NB4-2 cell. Thus, while the loss-of-function mutations in wg and slp have the same NB4-2 formation and specification defects, these defects in wg mutants can be rescued by expressing slp genes from a heterologous promoter. That slp genes function downstream of the Wg signaling is also indicated by the result that expression of slp genes is lost from the neuroectoderm in wg mutants and that ectopic expression of wg induces ectopic expression of slp. Finally, previous results show that Gooseberry (Gsb) prevents Wg from specifying NB4-2 identity to the wg-expressing NB5-3. In this paper, we also show that gsb interacts with slp and prevents Slp from specifying NB4-2 identity. Overexpression of slp overcomes this antagonistic interaction and respecifies NB5-3 as NB4-2. This respecification, however, can be suppressed by a simultaneous overexpression of gsb at high levels. This mechanism appears to be responsible for specifying NB5-3 identity to a row 5 neuroblast and preventing Wg from specifying NB4-2 identity to that cell.